Pengaruh Pembiayaan Jual Beli dan Pembiayaan Bagi Hasil Terhadap Laba Bersih Perusahaan - Nuri Purnama Sari; Mutiah Khaira Sihotang (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The aim of the research is to determine the effect of Buying and Selling Financing and Profit Sharing Financing on the Net Profit of Bank Muamalat Indonesia. This research uses a quantitative approach. The research population is the Financial Report of Bank Muamalat Indonesia and the sample chosen is the Financial Report of Bank Muamalat Indonesia in 2009-2022 with 56 quarters (13 years) recorded. The data analysis technique used is multiple linear regression analysis. The results of this research show that directly the Adjusted R Square (R2) value of 0.237 has a significant and partial influence between Buying and Selling Financing on the Financial Performance of Bank Muamalat Indonesia. However, there was no partial influence of Profit Sharing Financing but there was a significant positive influence of Profit Sharing Financing on the Net Profit of the Bank Muamalat Indonesia Company. Even so, between these two variables simultaneously and significantly there is an influence of Buying and Selling Financing and Profit Sharing Financing on the Net Profit of the Bank Muamalat Indonesia Company. Future researchers are expected to be able to develop research related to other Islamic Bank Financial Reports.